Evaluation of Bone Graft Need in Edentulous Posterior Sites: A CBCT Retrospective Study - Nourah, D. (Journal of Osseointegration, 2025)
Aim This retrospective study investigates the necessity for bone graft augmentation in edentulous posterior sites, focusing on the lower premolar and molar regions. Materials and Methods Using Cone Beam Computed Tomography (CBCT) imaging from patients treated at Umm Al-Qura University between 2019 and 2022, to evaluates bone conditions that influence dental implant placement. Digital software was employed to plan implant placement with a prosthetically driven approach. Measurement of buccal and lingual bone thickness at the coronal and middle aspect of the implant was done. Measurement less than 1mm was considered an indication for the need of bone augmentation. Results A total of 74 CBCT scans were evaluated, representing 100 missing teeth. Premolars constitute 23% (n=23), and molars constitute 77% (n=77) of the teeth site evaluated. A significant number of sites required bone grafting due to insufficient buccal bone thickness, with 80% of implants having <1mm bone thickness. 91% of premolar implants and 89.6% of molar implants lacked adequate buccal bone. More premolars needed guided bone regeneration (GBR) than molars (p<0.0001). Overall, 80% of implants needed bone grafts, with females showing a slightly higher need (p>0.05). Lingual bone thickness was adequate. Conclusion Number of edentulous posterior sites, specifically in the lower premolar and molar regions, necessitate bone graft augmentation for successful implant placement. Pre-surgical planning using digital software and CBCT imaging is crucial to assess bone accurately and determine the need for bone augmentation.